Tissue Engineering Strategies for Peripheral Nerve Regeneration - Li, Yin; Ma, Zhenjiang; Ren, Ya; Lu, Dezhi; Li, Tao; Li, Wentao; Wang, Jinwu; Ma, Hui; Zhao, Jie (Frontiers in Neurology, 2021)
Peripheral nerve injury (PNI) has severe and profound effects on the patient's life. The therapeutic approach remains one of the most challenging clinical problems. In recent years, many constructive nerve regeneration schemes have been proposed at home and abroad. Nerve tissue engineering plays an important role. It develops an ideal nerve substitute called artificial nerve. Given the complexity of nerve regeneration, this review summarizes peripheral nerve injury's pathophysiology and tissue-engineered repairing strategies. Moreover, we discussed scaffolds and seed cells for neural tissue engineering. Furthermore, we have also emphasized the role of 3D printing in tissue engineering.